Progress in Research on Antitumor Drugs and Dynamic Changes in Skeletal Muscles - Xu, Ting; Li, Zhen-Hao; Liu, Ting; Jiang, Cai-Hong; Zhang, Ya-Juan; Li, Hui; Jiang, Ying; Zhao, Juan; Guo, Wen-Jing; Guo, Jia-Yuan; Wang, Lu; Li, Jia-Xuan; et al. (Frontiers in Pharmacology, 2022)
Objective: To review the research progress of reltionship between antitumor drugs and the dynamic changes of the skeletal muscles during treatment phase. Background: Sarcopenia is a common disease in patients with tumors, and it has been agreed that patients with tumors and sarcopenia experience more serious adverse reactions and have a shorter long-term survival after antitumor therapy than patients without sarcopenia. Antitumor drugs whilst beneficial for tumor regression, interferes and synergizes with cancer-induced muscle wasting/sarcopenia, induced myodemia or intramuscular fat and the two conditions often overlap making it difficult to drive conclusions. In recent years, increasing attention has been paid to the dynamic changes in skeletal muscles during antitumor drug therapy. Dynamic changes refer not only measurement skeletal muscle quantity at baseline level, but give more emphasis on the increasing or decreasing level during or end of the whole treatment course. Methods: We retrievaled published English-language original research articles via pubmed, those studies mainly focused on repeated measurements of skeletal muscle index using computed tomography (CT) in cancer patients who received antitumor drug treatment but not received interventions that produced muscle mass change (such as exercise and nutritional interventions). Conclusion: This article will summarize the research progress to date. Most of antineoplastic drug cause skeletal muscle loss during the treatment course, loss of L3 skeletal muscle index is always associated with poor clinical outcomes.